2011
DOI: 10.1177/0897190011400549
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Medicine Pharmacy Practice

Abstract: Emergency medicine (EM) pharmacy practice has existed for over 30 years. In recent years, however, the specialty has grown significantly. A large number of health care systems have either a dedicated EM pharmacist or other clinical pharmacist presence in the Emergency department (ED). Over the past decade, the role of the EM pharmacist as a critical member of the health care team has expanded significantly and many innovative practices have evolved throughout the country. There is also some heterogeneity betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…physician assistants and ED scribes) suggests there might be some benefit to ED flow and efficiency . Allied Health Practitioners in referral models within EDs do little to improve congestion but value add; for example, clinical pharmacists within the ED reduce the number of medication errors and resulting adverse events, and radiographer‐led radiology services might reduce interpretive errors . A systematic review inferred that in some studies Care Coordination Teams were effective in reducing unnecessary social admissions in elderly populations and significantly reduced re‐presentations .…”
Section: Resultsmentioning
confidence: 99%
“…physician assistants and ED scribes) suggests there might be some benefit to ED flow and efficiency . Allied Health Practitioners in referral models within EDs do little to improve congestion but value add; for example, clinical pharmacists within the ED reduce the number of medication errors and resulting adverse events, and radiographer‐led radiology services might reduce interpretive errors . A systematic review inferred that in some studies Care Coordination Teams were effective in reducing unnecessary social admissions in elderly populations and significantly reduced re‐presentations .…”
Section: Resultsmentioning
confidence: 99%
“…1,2,[20][21][22][23] Pharmacists play active roles in creating programs that improve antimicrobial use, prevent adverse drug events, enhance pain and anticoagulation management, and optimize medication inventory. 23,24 Pharmacists' interventions have also been associated with cost avoidance. Lada et al 25 reported that during a 3-month period, the potential cost avoidance attributed to 1,393 pharmacist interventions was over $1 million.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, many institutions in most developed countries have pharmacists to review orders prospectively and this function provides significant safety benefits in the emergency department. [23] Furthermore, another study identified 7.8 medication errors per 100 patients and 2.9 per 100 medication orders were recovered by the emergency department pharmacists. Most of the recovered medication errors were intercepted potential ADEs (90.3%), with fewer mitigated ADEs (3.9%) and ameliorated ADEs (0.2%).…”
Section: Discussionmentioning
confidence: 99%